Neo-Colonization of Electoral Politics: Evidence from Hybrid Regime, Pakistan - Zia, Amir (International Journal of Psychosocial Rehabilitation, 2020)
The electoral politics is changing with dynamic interplay of electoral rhetoric, slogans and manifestoes under the influence of neo-liberal norms. The encompassing role of neo-liberal norms tend to facilitate hegemonic power dominance. In hybrid democracy Pakistan, military has been constantly pushing itself for achieving hegemonic power status to influence several policy preferences. These preferences are propagated through different political channels like policy preferences of political parties by formulating voter choices at different stages. The militarized hegemonic apparatus applies various strategies to consolidate political hegemony as manifestation of neo-colonization. The militarized hegemonic power structure tends to take firm control into economic field through covert facilitation of specific ‘political party’ as democratic smokescreen/façade. Political system laminated by ideology (Religion) is used to legitimize control of material conditions in the larger interest of hegemonic power structure. The rapid transmutation of mass opinion manufacturing through cyber means by information corporatized production have become effective tools. Therefore, contemporary political environment offers altogether different political resources to the military leaders of colonizing the political system by favoring one and constraining rest of political machines or parties. Thus, the structural shift of urbanization pushed commercialization that led to advanced form of capital accumulation produces adverse effects on the subordinate masses. The recent electoral event 2018 saw that high middle class and low-income groups got pushed into electoral rhetoric through populist notion ‘change’ by newly formed political vehicle Pakistan Tehreek i Insaf (PTI). Thereby, the concept of duality in dialectical contradiction and unity have become permanent feature of electoral politics in hybrid regime like Pakistan. Thereby finally, the electoral history shows several examples of governmental power under control of covert hegemonic actors as instruments of neo- colonization of electoral politics.